Method for rapidly simulating corrosion of metal material in atmosphere
By simulating the corrosion conditions of four seasons in the simulated environment, the problem of the corrosion of materials in the prior art is solved in different seasons or climatic conditions, and the accurate evaluation of the corrosion resistance and life of the materials is achieved.
Patent Information
- Application Number
- CN202411695293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to accurately simulate the corrosion conditions of materials under different seasons or climatic conditions, and it is impossible to effectively evaluate the corrosion resistance and life of materials.
A method to quickly simulate the corrosion of metal materials in the atmosphere is adopted. By conducting periodic corrosion tests in the simulated environment, the corrosion conditions in spring, summer, autumn and winter are simulated, including dust reduction tests, salt spray tests and drying tests, and factors such as temperature, humidity, rainfall and dust settlement are comprehensively considered.
It can more accurately simulate the corrosion conditions of materials in the atmospheric environment in a shorter time, evaluate the corrosion resistance and life of materials, and reveal the potential weaknesses of materials in specific seasons or climatic conditions.
Smart Images

Figure CN119643425A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of accelerated testing, in particular to a method for rapidly simulating corrosion of metal materials in the atmosphere. Background Art
[0002] Power facilities and equipment mainly include transmission systems (transmission lines, towers, etc.), substations (transformers, mutual inductors, etc.), distribution systems (distribution cabinets, distribution transformers, etc.), auxiliary equipment (power monitoring systems, communication equipment, etc.) and energy storage systems. Among the above equipment and facilities, except for a small amount of local materials, power grid equipment and facilities are mainly composed of metal parts such as copper, iron, and aluminum. When metal materials are exposed to severely polluted atmosphere, high-salt soil, and water sources in chemical environments, corrosion will cause material damage and equipment shutdown, thereby reducing power supply reliability, causing huge economic losses and social impacts. Therefore, the corrosion evaluation of power grid materials is of great significance to ensure the safe and reliable operation of power system facilities and equipment.
[0003] Traditional atmospheric corrosion research methods include atmospheric exposure tests and indoor accelerated tests. However, exposure tests in atmospheric environments usually take one to several years to obtain corrosion information of metal materials at a certain location. This long requirement is very unfavorable for assessing and accepting a certain product and evaluating the corrosion resistance of materials. Indoor accelerated tests have a short cycle and can simulate corrosion in different atmospheric environments, obtain data similar to real tests, and establish a life model for predicting atmospheric corrosion of materials. It is used for atmospheric corrosion behavior research of various steels and rapid evaluation of their corrosion resistance and life prediction.
[0004] The main indoor accelerated test methods currently used are the following: wet heat test, salt spray test, periodic spray composite corrosion test, dry-wet cycle test, etc. Dry-wet cycle test is widely used to study the corrosion behavior of various materials in natural environment. However, the infiltration process of this method cannot fully reproduce the atmospheric corrosion process, and does not take into account the phenomenon of seasonal changes.
[0005] Therefore, there is an urgent need to develop a corrosion test method that can accurately simulate the seasonal changes of materials and reveal the potential weaknesses of materials under specific seasons or climatic conditions, so as to more accurately reflect the corrosion conditions of materials in actual environments. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned defects and provide a corrosion test method that can accurately simulate the seasonal changes of materials.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention provides a method for rapidly simulating corrosion of metal materials in the atmosphere, comprising the following steps:
[0009] S1 sample pretreatment;
[0010] S2 placing the pretreated sample in a simulated environment for a periodic corrosion test, wherein the simulated environment includes at least one of a spring corrosion stage, a summer corrosion stage, an autumn corrosion stage, and a winter corrosion stage;
[0011] The corrosion stage of each season is tested in the order of "dust fall test → salt spray test → drying test";
[0012] S3: The sample corroded in step S2 is post-processed to obtain a sample to be tested, and the composition, corrosion rate and electrochemical performance of the product after the surface corrosion of the sample to be tested are analyzed.
[0013] The present invention adds the cycle of four seasons, the alternation of spring, summer, autumn and winter, to the simulated accelerated corrosion test of materials. Through the cycle of four seasons, the corrosion resistance of materials in different seasons can be evaluated, including the comprehensive influence of multiple factors such as temperature, humidity, rainfall and dust deposition. It is closer to the state of the sample surface during on-site exposure, and can reveal the potential weaknesses of materials in specific seasons or climatic conditions, helping to improve materials or take protective measures.
[0014] Preferably, the material of the sample includes but is not limited to Q235 carbon steel and 6061 aluminum alloy.
[0015] Preferably, the dust fall test comprises the following steps: 2 ·h) to the sample surface at a speed of 1-2h; wherein the simulated soil comprises the following components in parts by weight: 5-10 parts of calcium chloride, 40-50 parts of sodium sulfate, and 20-25 parts of potassium nitrate; and the diameter of the simulated soil particles is less than 500μm.
[0016] Preferably, the composition of the spray liquid for the salt spray test includes: 0.8-1.5wt% NaCl, 0.2-0.8wt% Na2SO4, and the balance is water.
[0017] Preferably, the temperature of the drying test is 45±3°C and the time is 3-4h.
[0018] In the present invention, the specific test environment in the simulated corrosion test in different seasons is different. Various factors such as temperature, humidity, rainfall, and dust deposition are comprehensively considered. The experimental scheme is adjusted according to the differences in temperature, humidity, and rainfall in the four seasons, and the corrosion conditions in different seasons are finally determined, which are as follows:
[0019] Preferably, the spring corrosion stage comprises the following steps in sequence:
[0020] (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h;
[0021] (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 25-30h;
[0022] (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
[0023] Preferably, the summer corrosion stage comprises the following steps in sequence:
[0024] (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h;
[0025] (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 40-45h;
[0026] (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
[0027] Preferably, the autumn corrosion stage comprises the following steps in sequence:
[0028] (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h;
[0029] (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 20-25h;
[0030] (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
[0031] Preferably, the winter corrosion stage comprises the following steps in sequence:
[0032] (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h;
[0033] (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 0.5-1.5h;
[0034] (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
[0035] Preferably, the pretreatment includes sample preparation, surface cleaning and drying. Specifically: (a) the sample obtained by sample preparation is in the form of flakes; (b) the surface cleaning is processed to a smoothness Ra ≥ 3.2, degreased and cleaned with a degreasing agent, and then further dehydrated with ethanol; (c) drying is performed at 25±5°C for > 24h.
[0036] Preferably, the phase combinations of the experimental cycle of the periodic corrosion test in step S2 include the order of "spring-summer-autumn-winter", "summer-autumn-winter-spring", "autumn-winter-spring-summer" or "winter-spring-summer-autumn".
[0037] It should be particularly noted that, in the present invention, the four stages can be carried out individually or in combination to simulate and evaluate the corrosion resistance of a certain season or several seasons, and adjusted according to the order of the four seasons. For example, it can be a combination of "spring", "summer", "autumn", "winter", "spring and summer", "summer, autumn and winter", etc.
[0038] Preferably, the number of cycles of the cycle in step S2 is a natural number between 1-4.
[0039] Preferably, the post-treatment in step S3 is to rinse the surface with alcohol and dry it with a hair dryer.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The present invention adds a four-season cycle to the accelerated test of simulated material corrosion, and comprehensively considers multiple factors such as temperature, humidity, rainfall, and dust deposition. The experimental plan is adjusted according to the differences in temperature, humidity and rainfall in the four seasons, and finally the corrosion conditions in different seasons are determined, which is closer to the state of the sample surface during on-site exposure. At the same time, it can also more accurately simulate the corrosion of materials in the atmospheric environment in a shorter time, providing strong support for material evaluation. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The macroscopic morphology of the Q235 carbon steel surface after 1 week, 2 weeks, 3 weeks, and 4 weeks of cyclic corrosion in the corrosion test of Example 1;
[0043] Figure 2In the corrosion test of Example 1, the scanning electron microscope microscopic morphology images of the Q235 carbon steel surface after 1 week (a), 2 weeks (b), 3 weeks (c), and 4 weeks (d) of cyclic corrosion are respectively taken;
[0044] Figure 3 is the corrosion curve of Q235 carbon steel in the corrosion test of Example 1;
[0045] Figure 4 This is an analysis diagram of the electrochemical performance of Q235 carbon steel during four-season corrosion cycles in Example 1;
[0046] Figure 5 The macroscopic morphology of the surface of 6061 aluminum alloy after 1 week, 2 weeks, 3 weeks, and 4 weeks of cyclic corrosion in the corrosion test of Example 2;
[0047] Figure 6 In the corrosion test of Example 2, the scanning electron microscope microscopic morphology images of the 6061 aluminum alloy surface after 1 week (a), 2 weeks (b), 3 weeks (c), and 4 weeks (d) of cyclic corrosion are respectively taken;
[0048] Figure 7 is the corrosion curve of 6061 aluminum alloy in the corrosion test of Example 2;
[0049] Figure 8 This is an analysis diagram of the electrochemical performance of 6061 aluminum alloy during four-season corrosion cycles in Example 2. DETAILED DESCRIPTION
[0050] For better explanation of the purpose, technical scheme and advantage of the present invention, the present invention will be further described below in conjunction with specific embodiment and accompanying drawing, but embodiment does not limit the present invention in any form.Unless otherwise specified, the reagent, method and equipment adopted in the present invention are conventional reagents, methods and equipment in the art.Unless otherwise specified, the reagents and materials used in the present invention are commercially available.
[0051] In the embodiments and comparative examples of the present invention, the composition of the simulated soil used is: a mixture of calcium chloride: sodium sulfate: potassium nitrate = 7:45:23 by weight, and after sieving, a mixture with a particle diameter of less than 500 μm is obtained.
[0052] In the embodiments and comparative examples of the present invention, the spray liquid used in the salt spray test contains 1.0 wt % NaCl and 0.5 wt % Na2SO4.
[0053] Example 1
[0054] This embodiment provides a method for quickly simulating the corrosion of metal materials in the atmosphere, comprising the following steps:
[0055] S1 Sample pretreatment
[0056] Q235 carbon steel (composition see Table 1) was used as the sample, and processed into a sheet sample with a size of 5 cm*2.5 cm and a thickness of 2 mm, and then ground and polished to a surface finish of Ra ≥ 3.2. The sample was degreased and dehydrated with ethanol, and after cleaning, it was placed at room temperature (25±5℃) and air-dried for 24 hours, and the initial mass m0 (in g) of the sample was weighed;
[0057] Table 1 Composition of Q235 carbon steel
[0058]
[0059] S2 performs a periodic corrosion test: the sample pretreated in step S1 is placed in a simulated environment and sequentially undergoes a spring corrosion stage, a summer corrosion stage, an autumn corrosion stage, and a winter corrosion stage. The four stages constitute a cycle. In each cycle:
[0060] The spring corrosion phase includes the following steps:
[0061] (1) Dust fall test: simulated soil was used with a dust concentration of 3 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1 h;
[0062] (2) The conditions of the salt spray test are: temperature 45±3℃, spray volume of spray liquid 1.0mL / (mm 2 ·h), spraying time is 28h;
[0063] (3) The conditions of the drying test are: temperature 45 ± 3 °C, drying for 3 h;
[0064] The summer corrosion stage includes the following steps:
[0065] (1) Dust fall test: simulated soil was used with a dust concentration of 3 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1 h;
[0066] (2) The conditions of the salt spray test are: temperature 45±3℃, spray volume of spray liquid 1.0mL / (mm 2 ·h), spraying time is 44h;
[0067] (3) The conditions of the drying test are: temperature 45 ± 3 °C, drying for 3 h;
[0068] The fall corrosion phase includes the following steps:
[0069] (1) Dust fall test: simulated soil was used with a dust concentration of 3 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1 h;
[0070] (2) The conditions of the salt spray test are: temperature 45±3℃, spray volume of spray liquid 1.0mL / (mm 2 ·h), spraying time is 23h;
[0071] (3) The conditions of the drying test are: temperature 45 ± 3 °C, drying for 3 h;
[0072] The winter corrosion phase includes the following steps:
[0073] (1) Dust fall test: simulated soil was used with a dust concentration of 3 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1 h;
[0074] (2) The conditions of the salt spray test are: temperature 45±3℃, spray volume of spray liquid 1.0mL / (mm 2 ·h), spraying time is 1h;
[0075] (3) The conditions of the drying test are: temperature 45 ± 3 °C, drying for 3 h;
[0076] S3 Corrosion Analysis
[0077] (1) Surface corrosion macromorphology: Use an optical magnifying glass to observe the macromorphology of corrosion. Figure 1 ; From the figure, it can be seen that at the beginning of corrosion, planar corrosion products appear on the surface of the sample, and the surface looks relatively uniform; as the test progresses, the corrosion products gradually change from planar to convex corrosion products. (2) Surface corrosion micromorphology: Scanning electron microscopy (SEM) was used to observe the micromorphology of corrosion, see Figure 2 ; From the figure, it can be seen that the corrosion products are relatively flat, but there are also local pitting corrosion products on its microscopic surface. As the test progresses, the pitting corrosion products on its surface change into needle-like or fibrous structures, and then the volume of the needle-like corrosion products increases, and the rust layer tends to become flat. (3) Corrosion rate analysis of materials:
[0078] The sample after corrosion in step S2 is cleaned of corrosion products on the surface of the sample according to the corrosion product removal standard in the standard "GB / T16545-2015 Corrosion of Metals and Alloys", and the surface is rinsed with alcohol and dried with a hair dryer to obtain a sample to be tested. The corrosion condition of the sample to be tested is analyzed as follows:
[0079] Measure the weight of the sample at different times during the corrosion process (recorded as m), and calculate the corrosion thickness loss of the sample by the following relationship:
[0080]
[0081] d is the corrosion thickness loss, μm;
[0082] m0 is the initial weight of the sample, g;
[0083] m is the weight of corrosion products removed from the sample after the corrosion test, g;
[0084] A is the surface area of the sample, which is 2800 mm 2 ;
[0085] ρ is the density of the sample, g / mm 3 ;
[0086] Then, the corrosion curve is obtained by taking time as the horizontal axis and thickness as the vertical axis, and the curve is fitted with a function to obtain the corrosion curve (see Figure 3 ), and found that the thickness loss (the thickness difference between any two moments) satisfies the relationship: d = 38.6 × t 0.88 , d represents the thickness loss of the sample at a certain moment (in μm), and t represents the time of the corrosion test (in cycles). It can be seen that the fitting relationship is an exponential function, which is more consistent with the corrosion in the actual atmospheric environment.
[0087] (4) Analysis of electrochemical performance during sample corrosion:
[0088] The electrochemical performance of the samples was analyzed using a CS electrochemical workstation. The test conditions of the electrochemical workstation were as follows: the scanning range was OCP ± 0.3 V, and the scanning speed was 0.5 mV / s. The test results are shown in Figure 4 ;from Figure 4 It can be seen that as the corrosion test period increases, the potentiodynamic polarization curve moves to the left, indicating that the corrosion current density decreases, indicating that the rust layer is increasingly protective of the metal substrate.
[0089] Example 2
[0090] This embodiment provides a method for quickly simulating the corrosion of metal materials in the atmosphere. The method of Example 1 is used for testing. The difference from Example 1 is that the material of the sample is replaced by 6061 aluminum alloy instead of Q235 carbon steel. The composition of 6061 aluminum alloy is shown in Table 2:
[0091] Table 1 6061 aluminum alloy composition
[0092]
[0093] The corrosion analysis results in step S3 are as follows:
[0094] (1) Surface corrosion macromorphology: Use an optical magnifying glass to observe the macromorphology of corrosion. Figure 5; It can be seen from the figure that the metal surface is covered with corrosion products. Due to the excellent corrosion resistance of aluminum alloy, the macroscopic morphology difference is small as the test time increases.
[0095] (2) Surface corrosion micromorphology: Scanning electron microscopy (SEM) was used to observe the micromorphology of corrosion. Figure 6 ; From the figure, we can see that in the early stage of aluminum alloy corrosion, pitting corrosion products appear on the metal surface. As the corrosion process continues, these pitting corrosion products gradually increase in size, and the height of the protrusions also increases with the accumulation of corrosion products.
[0096] (3) Corrosion rate analysis of materials:
[0097] The sample after corrosion in step S2 is cleaned of corrosion products on the surface of the sample according to the corrosion product removal standard in the standard "GB / T16545-2015 Corrosion of Metals and Alloys", and the surface is rinsed with alcohol and dried with a hair dryer to obtain a sample to be tested. The corrosion condition of the sample to be tested is analyzed as follows:
[0098] The thickness of the sample was measured at different times during the corrosion process, and then the corrosion curve was obtained with time as the horizontal axis and thickness as the vertical axis. The curve was fitted with a function to obtain the corrosion curve (see Figure 7 ), and found that the thickness loss (the thickness difference between any two moments) satisfies the relationship: d = 3.4 × t 0.91 , d represents the sample thickness at a certain moment (in μm), and t represents the time of the corrosion test (in cycles). It can be seen that the fitting relationship is an exponential function, which is more consistent with the corrosion in the actual atmospheric environment.
[0099] (4) Analysis of electrochemical performance during sample corrosion:
[0100] The electrochemical performance of the samples was analyzed using a CS electrochemical workstation. The test conditions of the electrochemical workstation were as follows: the scanning range was OCP ± 0.3 V, and the scanning speed was 0.5 mV / s. The test results are shown in Figure 8 ;from Figure 8 It can be seen that in the first three cycles of the test, the potentiodynamic polarization curve has a tendency to move slightly to the left, indicating that the formation of corrosion products at this time has a slight protective effect on the metal matrix; when the test was carried out to the fourth cycle, the curve suddenly shifted to the right compared with the third cycle, indicating that the protective performance of the corrosion product layer on the matrix decreased.
[0101] Example 3
[0102] This embodiment provides a method for quickly simulating the corrosion of metal materials in the atmosphere, and the test is performed with reference to the method of Embodiment 1. The difference from Embodiment 1 is that:
[0103] In step S2, the time of the salt spray test in each seasonal corrosion stage is changed as follows:
[0104] Spring: spray for 20 hours; Summer: spray for 40 hours; Autumn: spray for 24 hours; Winter: spray for 0.5 hours.
[0105] The corrosion situation in step S3 is similar to that in Example 1, where the fitting relationship of the corrosion curve is d=35.6×t 0.62 , which is also an exponential function and is closer to the actual corrosion situation.
[0106] Comparative Example 1
[0107] This comparative example provides a method for simulating the corrosion of a metal material in the atmosphere, and the test is performed with reference to the method of Example 1. The difference from Example 1 is that the corrosion method in each seasonal stage is performed in the order of "simulated precipitation test→drying test→salt spray test→drying test", and the conditions of the salt spray test and the drying test are consistent with those of Example 1. The specific operation of the simulated precipitation test is: spraying for 85 hours at a temperature of 45±1°C, the spraying liquid is deionized water, and the spraying rate is 20 mm / h;
[0108] In step S3, the morphological corrosion situation is similar to that in Example 1, but the fitting relationship of the corrosion curve is d=25.635×t, which is somewhat different from the actual corrosion rate trend and has a high degree of fit with the actual situation only in a short period of time, which is not conducive to corrosion prediction for a longer period of time.
[0109] Comparative Example 2
[0110] This comparative example provides a method for simulating the corrosion of metal materials in the atmosphere, and the test is performed with reference to the method of Example 1. The difference from Example 1 is that the four seasons are not distinguished, and the parameters of the "summer corrosion stage" in Example 1 are used, wherein the spraying time of the salt spray test is 96h;
[0111] In step S3, the morphological corrosion situation is similar to that in Example 1, but the fitting relationship of the corrosion curve is d==84.29×e 0.0995t , which is somewhat different from the actual corrosion rate trend, and the degree of fit with the actual situation is high only in a short period of time, which is not conducive to corrosion prediction for a longer period of time.
[0112] Comparative Example 3
[0113] This comparative example provides a method for simulating the corrosion of metal materials in the atmosphere, and the test is performed with reference to the method of Example 1. The difference from Example 1 is that in the periodic corrosion test of step S2, the "dust fall test" is not performed in the test of the corrosion stage of each season;
[0114] In step S3, the fitting relationship of the corrosion curve is d=20.15×t, the corrosion rate is slow, and there is a certain difference from the actual corrosion rate trend, and the prediction result is inaccurate.
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for rapidly simulating corrosion of metal materials in the atmosphere, characterized in that: The following steps are involved: S1 sample pretreatment; S2 placing the pretreated sample in a simulated environment for a periodic corrosion test, wherein the simulated environment includes at least one of a spring corrosion stage, a summer corrosion stage, an autumn corrosion stage, and a winter corrosion stage; The corrosion stage of each season is tested in the order of "dust fall test → salt spray test → drying test"; S3: The sample corroded in step S2 is post-processed to obtain a sample to be tested, and the composition, corrosion rate and electrochemical performance of the product after the surface corrosion of the sample to be tested are analyzed.
2. The method for rapidly simulating corrosion of metal materials in the atmosphere according to claim 1, characterized in that: The dust fall test comprises the following steps: 2 h) to the surface of the sample and settle for 1-2h; Wherein, the simulated soil comprises the following components in parts by weight: 5-10 parts of calcium chloride, 40-50 parts of sodium sulfate, and 20-25 parts of potassium nitrate; The diameter of the simulated soil particles is less than 500 μm.
3. The method for rapidly simulating corrosion of metal materials in the atmosphere according to claim 1, characterized in that: The composition of the spray liquid for the salt spray test includes: 0.8-1.5wt% NaCl, 0.2-0.8wt% Na2SO4, and the balance is water.
4. The method for rapidly simulating corrosion of metal materials in the atmosphere according to claim 1, characterized in that: The temperature of the drying test is 45±3°C and the time is 3-4h.
5. The method for rapidly simulating corrosion of metal materials in the atmosphere according to any one of claims 1 to 4, characterized in that: The spring corrosion stage comprises the following steps in sequence: (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h; (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 25-30h; (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
6. The method for rapidly simulating corrosion of metal materials in the atmosphere according to any one of claims 1 to 4, characterized in that: The summer corrosion stage comprises the following steps in sequence: (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h; (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 40-45h; (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
7. The method for rapidly simulating corrosion of metal materials in the atmosphere according to any one of claims 1 to 4, characterized in that: The autumn corrosion stage includes the following steps in sequence: (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h; (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 20-25h; (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
8. The method for rapidly simulating corrosion of metal materials in the atmosphere according to claim 1, characterized in that: The winter corrosion stage includes the following steps in sequence: (1) The dust fall test conditions are: using simulated soil with a particle diameter of less than 500 μm and a dust concentration of 3-5 μg / (mm 2 h) to the surface of the sample, and the dust settling time is 1-2h; (2) The conditions of the salt spray test are: temperature 45±3℃, salt spray deposition 1.0-1.5mL / (mm 2 ·h), spraying time is 0.5-1.5h; (3) The conditions of the drying test are: temperature 45±3℃, drying 3-4h.
9. The method for rapidly simulating corrosion of metal materials in the atmosphere according to claim 1, characterized in that: Satisfies at least one of the following characteristics: (1) The pretreatment includes sample preparation, surface cleaning and drying; (2) The phase combinations of the experimental cycle of the periodic corrosion test in step S2 include: the order of "spring-summer-autumn-winter", "summer-autumn-winter-spring", "autumn-winter-spring-summer" or "winter-spring-summer-autumn"; (3) The number of cycles in step S2 is a natural number between 1 and 4.